2016
DOI: 10.3354/meps11787
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dynamics of the green sea urchin Strongylocentrotus droebachiensis in food‑depleted habitats

Abstract: Supplement 1 Methods 1. Collection and maintenance of urchins Urchins used in Experiment 1 and Experiment 2 were hand collected by divers at depths of 3 to 6 m in the barrens at Bread and Cheese Cove (BCC) in January, June, and July 2012. They were transported in large containers filled with seawater to the Ocean Sciences Centre (OSC) of Memorial University of Newfoundland. Upon arrival at the OSC (<5 hours after collection), urchins were transferred to 330-L holding tanks supplied with ambient flow-through se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…It is known that with increasing water velocity (higher than approximately 15 cm s -1 ), sea urchins decrease their displacement and cease feeding both under laboratory (Kawamata, 1998; Frey & Gagnon, 2016; Cohen-Rengifo et al, 2018; Tamaki, Muraoka & Inoue, 2018) and field (Lissner, 1980; Dance, 1987; Siddon & Witman, 2003; Dumont, Himmelman & Russell, 2006; Dumont, Himmelman & Robinson, 2007) conditions. Escape behavior was also observed in laboratory flume experiments: at flow velocity ≤30 cm s −1 , sea urchins moved in a downstream direction whereas at 35–45 cm s −1 , individuals moved in an upstream direction (Morse & Hunt, 2013; Cohen-Rengifo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that with increasing water velocity (higher than approximately 15 cm s -1 ), sea urchins decrease their displacement and cease feeding both under laboratory (Kawamata, 1998; Frey & Gagnon, 2016; Cohen-Rengifo et al, 2018; Tamaki, Muraoka & Inoue, 2018) and field (Lissner, 1980; Dance, 1987; Siddon & Witman, 2003; Dumont, Himmelman & Russell, 2006; Dumont, Himmelman & Robinson, 2007) conditions. Escape behavior was also observed in laboratory flume experiments: at flow velocity ≤30 cm s −1 , sea urchins moved in a downstream direction whereas at 35–45 cm s −1 , individuals moved in an upstream direction (Morse & Hunt, 2013; Cohen-Rengifo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, water flow regimes, even during that time of year (September to December) when wave energy typically increases in southeastern Newfoundland (Brodie et al 1993, Blain & Gagnon 2013, Frey & Gagnon 2016, did not differ between depths. In fact, water flow was generally low throughout the survey, with a few peaks between 0.2 and 0.3 m s -1 at 12 m that lasted only a few hours in November.…”
Section: Hydrodynamic Environmentmentioning
confidence: 96%
“…However, since Marrack's pioneering demonstration of bioturbation in a Californian rhodolith bed (Marrack 1999 tens of podia to displace, but unlike the common sea star, the green sea urchin also moves large numbers of spines as it displaces, often bracing them into cracks and crevices to gain purchase (Frey & Gagnon 2016). Moreover, adult-sized common sea stars like those in the present study are considerably larger than rhodoliths and their five arms largely conform to the shape of objects on which they displace.…”
Section: Bioturbationmentioning
confidence: 99%
“…Scheibling and Hamm (1991) reported that sea urchins greatly favored clusters of boulders over an adjacent cobble bed, since these microhabitats offered shelter form predation. On more uniform bedrock bottoms, S. droebachiensis also prefers microhabitats that favor anchorage, such as crevices, troughs and boulders, in the attempt to minimize dislodgement (Frey & Gagnon, 2016). Whether to avoid predation or dislodgement, structurally complex microhabitats drove the urchin distribution at our study site on the rocky matrix but also on sandy bottoms by locally enhancing the heterogeneity.…”
Section: Discussionmentioning
confidence: 99%